Comparison of two identification and susceptibility test kits for Ureaplasma spp and Mycoplasma hominis in amniotic fluid of patients at high risk for intra-amniotic infection. (17th October 2020) - Kusanovic, Juan Pedro; Vargas, Paula; Ferrer, Fernando; Díaz, Francisco; Córdova, Víctor; Martinovic, Carolina; Valdés, Rafael; Rosas, Alejandra; Luna, Daniela; Silva, Pablo; Silva, Karla; Nilo, María Elena; et al.
Abstract: Objective: Ureaplasma urealyticum and Mycoplasma hominis are the most common microorganisms found in the amniotic fluid of patients at risk for preterm delivery. However, culture techniques for genital mycoplasms require special conditions, are barely considered as part of the evaluation of suspected intra-amniotic infection (IAI) and the results are available within 2 and 7 days. The objectives of this study are to validate the use of two commercially available kits (Mycoplasma IES y MYCOFAST ® RevolutioN) for the identification of Ureaplasma spp. and Mycoplasma hominis in amniotic fluid, to compare the results of these kits with those obtained by culture and real-time polymerase chain reaction (qPCR) and to report the antibiotic sensitivity profile of the genital mycoplasms identified. Methods: This is a prospective cohort study including women with singleton and twin gestations between 16 and 36 weeks. Patients were admitted to perform an amniocentesis due to pregnancy complications considered at high risk for IAI (e.g. preterm labor with intact membranes, preterm prelabour rupture of membranes, short cervix, etc.), treatment of polyhydramnios, and for the assessment of fetal death and fever without a focus. Results: Overall, 93 patients underwent amniocentesis and 63 had results available for all tests. The prevalence of a positive culture was 6% (4/63). There were four cases of Ureaplasma spp. and none of Mycoplasma hominis . The qPCR identified one case as Ureaplasma spp., one case as Ureaplasma parvum and two cases as Ureaplasma urealyticum . For all tests, the diagnostic performance was as follows: sensitivity 100% [95% CI (39.8–100%)], specificity 100% [95% CI (93.9–100%)], positive predictive value 100% [95% CI (39.8–100%)] and negative predictive value 100% [95% CI (93.9–100%)]. In this cohort, Ureaplasma spp. showed low resistance to erythromycin, but a high resistance to clindamycin and clarithromycin that may change according to the antibiotic concentration. Conclusions: To our knowledge, this is the first study that validates the use of the Mycoplasma IES and MYCOFAST ® RevolutioN kits for the identification of genital mycoplasmas in amniotic fluid. The results of these kits are mostly available within 24 hours, have an excellent correlation with those from broth cultures and qPCR and characterize the antibiotic sensitivity profile of the genital mycoplasms identified, providing an opportunity for specific treatment in cases of IAI. Further validation studies in other populations are needed.